Edge of battle Mcnab's got serious company - Brown, Dale (London HarperCollins publishers, 2006)
Violence has erupted on the border between the United States and Mexico, caused by rival drug lords.Major Jason Richter along with the members of task force TALON set up a base in Southern California called Operation Rampart,with the aim of crushing the unrest. But their presence causes controversy, and suddenly events begin to take a very menacing turn.Ernesto Fuerza, nicknamed Commander Veracruz has reinvented himself as a Mexican freedom fighter and is intent on causing mayhem by declaring the treaty that gave the Northern most Mexican states to the US, illegal. However, his motives are far from honourable and hide a sinister plot to flood the US with drugs.Re-assigned to the FBI to investigate the murders of several border patrolmen in Southern California, Task Force TALON uncover Fuerza's real intentions. As Richter and his team are coaxed across the border into Mexico, tension between the two countries explodes into violence and an all out guerrilla war-fare threatens to destroy the very fabric of the USA.Only Richter and his seasoned gang of professionals can stop the carnage. But is it already too late?